Potential Cytotoxic Activity of Methanol Extract, Ethyl Acetate, and n-Hexane Fraction from Clitoria ternatea L. on MCF-7 Breast Cancer Cell Line and Molecular Docking Study to P53 - Rollando Rollando; Muhammad Hilmi Afthoni; Marsha Anggita Amelia; Kestrilia Rega Prilianti (Chemistry Department, The University of Brawijaya, 2023)
Breast cancer is a condition where the cells in breast tissue lose control and multiply uncontrollably. In this study, MCF-7 breast cancer cells were tested for cytotoxic activity using the MTT assay and the active compound's interaction with the p53 protein was tested in silico. The most active fraction was found to be the ethyl acetate fraction, with an IC50 value of 1.730 μg/mL and a selectivity index of 2.485. However, the selectivity index was less than 3, and Vero cells showed changes in morphology with the addition of the ethyl acetate fraction. GC-MS was used to identify 19 compounds in the ethyl acetate fraction, and in-silico tests were performed on 5 potential anticancer compounds. Lipinski's Rule of Five test showed that only 3 of these compounds could undergo molecular docking. The results indicated that Anethole compound can interact with p53 protein, while Cinnamaldehyde, (E)- can interact with p21 protein.